Isolation and structural characterization of mannanoligosaccharides from aqueous palm kernel cake extract - Kalidas, Reddy Naveena (2016)
Palm kernel cake (PKC) is the most valuable by-product obtained from the palm kernel oil extraction process. It has been used widely as an animal feed owing to its high protein content. PKC also contains about 81% of non-starch polysaccharides, mainly in the form of mannan-based polymers. Hydrolysis of mannan into low molecular weight mannanoligosaccharides (MOS) has been claimed to have prebiotic properties. The biological mechanism and activities of the MOS are associated with its structure and molecular weight. However, very little information was available on the structural characteristics of MOS of different molecular weights from PKC. Therefore, the objectives of the present study were to isolate MOS of different degree of polymerization (DP) from the crude PKC extract and structurally characterize the MOS using chemical derivatization and spectroscopic methods. The crude PKC extract was obtained by hot water extraction method, followed by delipidation and deproteinization step. The deproteinized PKC extract containing mixtures of MOS were then separated into individual compounds based on their molecular weights using refractive index high performance liquid chromatography (RI-HPLC). The molecular weights of the MOS were determined using electrospray ionization mass spectrometry (ESI-MS/MS). The structures of the isolated MOS were investigated using a combination of chemical analyses such as sugar composition analysis and methylation analysis followed by gas chromatography mass spectrometry (GC-MS), and other spectroscopic methods such as nuclear magnetic resonance spectroscopy (NMR). The MOS mixtures were separated into four individual major compounds with different DP, designated as MOS-III, MOS-IV, MOS-V and MOS-VI. The molecular weights of the isolated MOS as determined by ESI-MS/MS were 689, 851, 1013 and 1151 Dalton (Da) corresponding to tetra-, penta-, hexa- and heptasaccharide of the MOS-III, MOS-IV, MOS-V and MOS-VI, respectively. Sugar analysis of the isolated MOS indicated the presence of mannose in each of the oligomers. Methylation and 1D/2D NMR analysis showed that the MOS have a linear structure consisting of (1→4)-β-D-mannopyranosyl residues with DP ranging from 4 to 7. They were identified as: a) β-D-Manp-(1→4)-β-D-Manp- (1→4)-β-D-Manp-(1→4)-β-D-Manp, b) β-D-Manp-(1→4)-β-D-Manp-(1→4)-β-D Manp-(1→4)-β-D-Manp-(1→4)-β-D-Manp, c) β-D-Manp-(1→4)-β-D-Manp-(1→4)-β- D-Manp-(1→4)-β-D-Manp-(1→4)-β-D-Manp-(1→4)-β-D-Manp, d) β-D-Manp- (1→4)-β-D-Manp-(1→4)-β-D-Manp-(1→4)-β-D-Manp-(1→4)-β-D-Manp-(1→4)-β-DManp-( 1→4)-β-D-Manp. In conclusion, the present study revealed a successful application of chromatography, chemical analysis, ESI-MS/MS and NMR to the isolation and characterization of MOS fraction from PKC.